Sustainability Of External Debt : The Case Of Malaysia - Fatmawaty, A Fattah (Universiti Malaysia Sarawak (UNIMAS), 2016)
The study examines the sustainability of external debt in Malaysia. The model built for the study proxy external debt as the measuring as a function of economic growth, foreign direct investment (FDI), inflation and money and quasi money. Annual time series data was gathered from the International Monetary Fund (IMF) and data from World Development Indicators (World Bank) from 1980 to 2013. The econometric techniques of Ordinary Least Square (OLS), Unit Root Test, Johansen Cointegration Test, Error Correction Method (ECM), Variance Decomposition, and Impulse Response are employed in the empirical analysis. The cointegration test shows that there is a long-run equilibrium relationships exist among the variables. The findings from the error correction method show that there is short run relationship running from M2 and external debt. While FDI granger cause external debt in short run. In this paper, long run results shows external debt and economic growth will responsible to the adjustment of equilibrium.